2022
DOI: 10.31869/rtj.v5i1.3068
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Penggunaan Modul Berbasis Projeck Based Learning Dalam Pembelajaran Teknologi Alat Berat

Abstract: Learning requires support from a reliable media, one of which can be a learning module. Based on several previous studies regarding the module, there are still some shortcomings from the module under study. So that further development of the given module is needed by adding the contents of the module using the project. This study aims to examine the development of heavy equipment technology modules including validity tests, practicality tests and project-based effectiveness tests. This research is included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…In line with research says that teaching materials that are well developed using a fairly good approach method, students will be active so that increased understanding of knowledge and skills possessed because the problems given are directly related to the conditions in the field (Natalia & Jalinus, 2021;Putra et al, 2022;Syah et al, 2019). In line with research, regarding the effectiveness of developing teaching materials, it was found that the development of innovative teaching materials will make students more open and creative in learning (Hsin & Wu, 2023;Mirah Setia Dewi et al, 2019;Pursitasari et al, 2022).…”
Section: Discussionmentioning
confidence: 84%
“…In line with research says that teaching materials that are well developed using a fairly good approach method, students will be active so that increased understanding of knowledge and skills possessed because the problems given are directly related to the conditions in the field (Natalia & Jalinus, 2021;Putra et al, 2022;Syah et al, 2019). In line with research, regarding the effectiveness of developing teaching materials, it was found that the development of innovative teaching materials will make students more open and creative in learning (Hsin & Wu, 2023;Mirah Setia Dewi et al, 2019;Pursitasari et al, 2022).…”
Section: Discussionmentioning
confidence: 84%
“…Pembelajaran berbasis proyek mengarahkan peserta didik untuk merancang, membuat dan menghasilkan karya/hasil untuk mencapai kompetensi kognitif, sikap dan keterampilan (Banawi, 2019;Widiastuti et al, 2021). E-modul berbasis Project Based Learning adalah pembelajaran aktif yang menghubungkan teknologi ke dalam kehidupan sehari-hari dengan melakukan kegiatan proyek dan menciptakan karya (Khairani et al, 2022;Putra et al, 2022;Ramadhanti et al, 2022). Model PjBL dipilih sebagai model pembelajaran dalam E-modul ini dikarenakan pembelajaran dengan PjBL memberikan manfaat.…”
Section: Pendahuluanunclassified